PENGARUH SALES PROMOTION DAN PHYSICAL ENVIRONMENT DALAM MEMBANGUN BRAND EQUITY TERHADAP CONSUMER REPURCHASE INTENTIONSGERAI ICY BLUE DI SURABAYA - SOETANTO, ARNOLD (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this research was to analyze the effect of sales promotion and physical environment from Icy Blue outlets could build the brand equity which resulted an increase in consumer repurchase intentions of Icy Blue outlets in Surabaya. This research used causal research which is for finding and describing the cause-effect relationship and the influence of this research’s variables to be concluded. This research used primary data which obtained through questionnaires to the respondents. The sample size were 100 respondents and taken with purposive sampling techniques. The data analysis using Structural Equation Modeling (SEM) through LISREL’s program version 8.70 The results of this research indicate that sales promotion offered by Icy Blue outlets afford to increase the brand equity of Icy Blue outlets. And the brand equity that is formed could increase the consumer repurchase intentions of Icy Blue outlets in Surabaya. While the physical environment of Icy Blue outlets was not able to increase the brand equity.